Comparison of the protection of ferrets against pandemic 2009 influenza A virus (H1N1) by 244 DI influenza virus and oseltamivir - Dimmock, Nigel J.; Dove, Brian K.; Meng, Bo; Scott, Paul D.; Taylor, Irene; Cheung, Linda; Hallis, Bassam; Marriott, Anthony C.; Carroll, Miles W.; Easton, Andrew J. (Antiviral research, 2012)
► We compared the ability of DI RNA and Tamiflu to protect ferrets from influenza. ► We treated ferrets with one 2μg intranasal dose of DI RNA delivered as DI virus. ► Or we treated ferrets with 10 oral doses of Tamiflu totalling 25mg over 5days. ► Pandemic A/California/04/09 amplified the DI RNA by >25,000-fold. ► DI virus was more effective than Tamiflu in combatting pandemic A/California/04/09. The main antivirals employed to combat seasonal and pandemic influenza are oseltamivir and zanamivir which act by inhibiting the virus-encoded neuraminidase. These have to be deployed close to the time of infection and antiviral resistance to the more widely used oseltamivir has arisen relatively rapidly. Defective interfering (DI) influenza virus is a natural antiviral that works in a different way to oseltamivir and zanamivir, and a cloned version (segment 1 244 DI RNA in a cloned A/PR/8/34 virus; 244/PR8) has proved effective in preclinical studies in mice. The active principle is the DI RNA, and this is thought to interact with all influenza A viruses by inhibiting RNA virus synthesis and packaging of the cognate virion RNA into nascent DI virus particles. We have compared the ability of DI virus and oseltamivir to protect ferrets from intranasal 2009 pandemic influenza virus A/California/04/09 (A/Cal, H1N1). Ferrets were treated with a single 2μg intranasal dose of 244 DI RNA delivered as 244/PR8 virus, or a total of 25mg/kg body weight of oseltamivir given as 10 oral doses over 5days. Both DI virus and oseltamivir reduced day 2 infectivity and the influx of cells into nasal fluids, and permitted the development of adaptive immunity. However DI virus, but not oseltamivir, significantly reduced weight loss, facilitated better weight gain, reduced respiratory disease, and reduced infectivity on days 4 and 6. 244 DI RNA was amplified by A/Cal by >25,000-fold, consistent with the amelioration of clinical disease. Treatment with DI virus did not delay clearance or cause persistence of infectious virus or DI RNA. Thus in this system DI virus was overall more effective than oseltamivir in combatting pandemic A/California/04/09.